Acccounting Information System and Digital Marketing Assitance for MSMEs in Rungkut Surabaya - Hanny Purnomo; Yenny Sugiarti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Nine MSMEs in Rungkut and its surroundings have the same general problems, including production processes that are still not standardized, limited marketing facilities, and an understanding of business management and financial management so that they cannot compete with manufacturers. Even though many products have superior products. This is due to limited capital, equipment, and a lack of understanding of financial management. To overcome the problem of limited understanding regarding financial management and modern media marketing, a simple accounting information system training was held. The objectives of this training are to: 1) increase understanding of SME actors about the income and expenditure cycle; 2) understand modern marketing alternatives using social media and online platforms; and 3) increase understanding of simple financial management. The results of the training show that there is an increased understanding of these three things. SMEs are starting to understand the importance of internal control in their business cycle, knowing various online marketing media that can be used, understanding the concept of business entities, and the importance of recording financial transactions